TEACHING PRACTICE OF THE QUR'AN THEMATIC STUDY OF TAFSIR JALALAIN IN THE HOUSE OF THE QUR'AN AT-THIBYAN AND THE HOUSE OF THE QUR'AN HAFSHAH BINT UMAR - Zakaria, Aceng; Setiawan, Budi; Muslim, Muslim (STAI Al-Hidayah Bogor, 2024)
This service activity aims to introduce a thematic-based teaching method of the Qur'an using Tafsir Jalalain in two Qur'an Houses (RQ) in Bogor Regency, namely RQ At-Tibyan Peduli Indonesia in Cibinong District and RQ Hafshah Binti Umar in Tamansari District. This thematic teaching method is designed so that students not only understand the verses of the Qur'an literally, but also be able to relate them to the themes of daily life, so that learning becomes more relevant and applicable. This program is carried out through a participatory method that involves teachers and students actively in the learning process. The stages of the activity include teacher training, the implementation of learning with thematic studies, and evaluations to measure the effectiveness of the methods applied. The results of the activity showed that there was an increase in students' understanding of the meaning of the verses of the Qur'an in a practical daily context. The active participation of students in thematic discussions strengthens their involvement in learning, which can be seen from their high interest and motivation to learn. Students also show a better ability to relate Qur'anic values to their personal experiences, which has the potential to form a strong Islamic character. Based on these positive results, the thematic teaching method based on Tafsir Jalalain is expected to be an effective model that can be adopted by various other Islamic educational institutions in Indonesia to enrich students' understanding of the Qur'an and support the formation of Islamic characters that are relevant to the challenges of modern life